A variational approach to multiplicity results for boundary-value problems on the real line. Issue 1 (30th January 2015) - Bonanno, Gabriele; Barletta, Giuseppina; O'Regan, Donal
Abstract : We study the existence and multiplicity of solutions for a parametric equation driven by the p -Laplacian operator on unbounded intervals. Precisely, by using a recent local minimum theorem we prove the existence of a non-trivial non-negative solution to an equation on the real line, without assuming any asymptotic condition either at 0 or at ∞ on the nonlinear term. As a special case, we note the existence of a non-trivial solution for the problem when the nonlinear term is sublinear at 0. Moreover, under a suitable superlinear growth at ∞ on the nonlinearity we prove a multiplicity result for such a problem.